Sanitasi Kandang Ayam Potong Dengan Kepadatan Lalat Di Kecamatan Gantarang Kabupaten Bulukumba - Syafwan, Mahdiya Nabila; Erlani, Erlani; Rasman, Rasman (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Chicken coop sanitation is an effort to prevent disease by eliminating or managing environmental factors related to the chain of disease transmission. Sanitation is very important because if sanitation is problematic it will have an impact on the environment of the cage and the animals in the cage. The aim of the study was to determine the relationship between the sanitation of broiler chicken coops and the density of flies in Gantarang District, Bulukumba Regency. The type of research used in this research is analytical research, with a cross sectional approach with a total sample of 43 and analyzed using the chi square test. The results showed that there was a relationship between cage cleanliness and fly density level p = 0.000 < α = 0.05 and X2hit 25,077 X2tabel 3,841, there was a relationship between waste management and fly density level p = 0.000 <α= 0.05 and X2 tabel 43,000 > X2tabel 3.841, there is a relationship between disinfection and the density of flies p = 0.000 < α = 0.05 and X2hit 43,000 > X2 tabel 3.841, there is a relationship between humidity and the density of flies p = 0.000 <α= 0.05 and X2 hit 32.434 < X2 tabel 3.841. The conclusion of this study is that there is a relationship between cage cleanliness, waste management, disinfection, and humidity with fly density. It is hoped that broiler breeders will improve cage sanitation in terms of cage cleanliness, waste management, and disinfection. Keywords: Flies, Chicken Coop, Cage Cleanliness, Waste, Disinfection and humidity.